Gamification in L2 Vocabulary Acquisition for Primary Education: A Systematic Literature Review (2019–2024) - Fitri Budiarti; Akbar Al Masjid; Elyas Djufri (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
The acquisition of second language (L2) vocabulary in primary education faces significant hurdles due to cognitive demands and declining student engagement. This Systematic Literature Review (SLR) evaluates the effectiveness, motivational impact, and implementation challenges of integrating gamification into L2 vocabulary learning for primary students. Guided by PRISMA protocols, 25 high-impact journal articles published between 2019 and 2024 were analyzed. The results indicate that gamification significantly enhances both short-term recall and long-term retention compared to conventional methods. Key findings reveal that the "Points, Badges, and Leaderboards" (PBL) triad effectively satisfies psychological needs for competence and autonomy, while immediate feedback loops are critical for maintaining a "flow" state. Furthermore, gamification reduces "Foreign Language Anxiety" by creating a safe-to-fail environment. Despite challenges such as the "novelty effect" and infrastructure gaps, the study concludes that pedagogical integration—where teachers mediate digital tools is the primary driver of success. These findings offer a robust framework for educators to optimize early childhood language acquisition through gamified blended learning.